A fluorescent probe with a large Stokes shift for sensing sulfite in dry white wine based on pyrazolo[1, 5-a]pyridine fluorophore. (20th July 2021) - Ma, Chuanjun; Zhang, Liqing; Hou, Linlin; Chen, Fahong; Liu, Aikun; Ji, Ruixue; Wang, Qingfeng; Yuan, Chunhao; Ge, Yanqing
Graphical abstract: Highlights: A sulphite probe based on novel fluorophore pyrozolo[1, 5- a ]pyridine was designed. The probe exhibits highly sensitivity and selectivity toward SO2 . The probe can be applied to determine SO2 in dry white wine. Abstract: A new fluorophore pyrazolo[1, 5- a ]pyridine with a large Stokes shift was designed, synthesized and used to sense sulphite in dry white wine. This probe showed not only high sensitivity and selectivity but also exhibited a fast response to SO3 2− within 30 s.